PERAN KOMUNIKASI ORGANISASI DAN MOTIVASI DALAM MENINGKATKAN KINERJA BEM FEB UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Murtakiyah, Wardah; Widiarti, Dian; Rahman, Ervina Adita; Hamida, Lutfiyatil; Sari, Putri Ayu Purnama; Abdullah H.R.M, Farukh (Fakultas Ekonomi dan Bisnis, 2024)
Student organization is a forum or means for students to increase knowledge and improve their intellectual and personal welfare in order to achieve university goals. One of the important aspects in an organization is its performance, because performance plays a very important role in the running of organizational activities. Aspects that can support to improve performance are organizational communication and motivation. This study aims to determine the role of organizational communication and motivation in improving the performance of BEM FEB UNARS. This research method uses qualitative methods with structured and closed interview techniques. This interview was conducted with 3 students who were directly involved in the BEM FEB organization. The results showed that organizational communication and motivation greatly affect the performance of BEM FEB.